Improving Digital Literacy through Population Data Management Information System in Sawah Lebar Baru Subdistrict Bengkulu City - Renaningtias, Nurul; Vatresia, Arie; Putri, Tiara Eka; Kusuma, Teguh Nata; Ibrahim, Tanimu Adam (CV Media Inti Teknologi, 2025)
This activity aims to build a population data management information system at the website-based sub-district office. This activity is motivated by the results of observations made at the Sawah Lebar Baru District office, information governance is still carried out manually by recording in ledgers that still rely on conventional bookkeeping. This performance approach is considered less effective and efficient. This impacts public services, which take a long time and often make mistakes in recording and reporting information on the state of the community. The implementation method is identification of needs, preparation and development of the system, training and technical assistance, then implementation and monitoring. After the training, an evaluation was carried out to measure the increase in participants' knowledge and skills in using the system. Based on the post-test results, the average value was in the range of 80-90%, which indicates an increase in participants' understanding and abilities. Through this activity, population data management becomes more effective and efficient and services to the community become more optimal.